Análise de documentos curriculares da cidade de São Paulo quanto à utilização do raciocínio proporcional - Silva, Thiago Mascára da (2020)
This research aims to answer the main question: How the Learning and Development Objectives of the São Paulo Curriculum of Mathematics and the proportionality activities developed in the City of Knowledge and Learning (both from the seventh year), can contribute to the development of proportional reasoning? Our corpus of analysis are curricular documents produced by the Municipal Education Secretariat of São Paulo. The analysis of the curriculum documents is contained in two articles in this dissertation in a multipaper format that used the qualitative research methodology of documentary character. For the analyzes we used studies as a theoretical reference Lesh; Post & Behr (1988). We conclude that proportional reasoning can be developed in the Learning and Development Goals from the use of the proportion problems indicated by the aforementioned authors even in content other than proportion, because proportionality as a fundamental idea of mathematics provides applications in other contexts. In relation to the Notebook of the City Knowledge and Learning, we used categories of analysis that emerged from the concepts of proportional reasoning of the same authors and concluded that of eight units that the material presents, seven have activities of proportionality that present in their statements characteristics that stimulate development proportional reasoning.